Pelatihan Pembuatan Susu Kefir di Desa Giripurno Kota Batu Malang - Putri, Nabilah Pratama; Saputro, Erwan Adi; Panjaitan, Renova (LPPM Universitas Trunojoyo Madura, 2023)
Kefir milk is one of the fermented products of milk which contains lactic acid bacteria and yeast. Kefir milk is a functional and probiotics drink. Giripurno Village is one of the suppliers of pure cow's milk in the KUD in Batu City. Milk which produced by the residents of Giripurno Village is still not being utilized optimally, because milk marketing only depends on cooperatives. The main objective of community service activities is to maximize the utilization of milk through training related to milk processing, especially for making kefir milk. The community service method includes several stages, such as the discussion stage and field observation, the preparation stage, and the training stage. The results of the activity are increasing knowledge of the Giripurno Village community, especially the Dasa Wisma women's group about kefir milk products and increasing skills for making kefir milk products. The conclusion that can be given from this community service is the group of women feel educated and helped in finding ideas for processing cow's milk. The recommendations are required for an innovation to improve the taste of kefir milk and assistance in product manufacturing.